Well-being and Perceived Social Support among Kashmiri College Students - Waseem Qayoom Kachroo; G.Ramanathan (RADJA PUBLIKA, 2023)
Abstract The present study was a cross-sectional study. The main aim of present study was to explore the significance well-being among college students of Kashmir valley. The data were collected from students 480 students from various degree colleges of Kashmir (21-24 years old age). The data was analyzed by computing Pearson’s correlation to test the relationship between study variables. The main intent was to estimate relationship between perceived social supports with well-being. The well-being questionnaire and perceived social support questionnaire were administrated. Results demonstrated that there was significant difference was found on the basis of gender, area of residence and family monthly income. Findings also indicated that there is a perceived social support is positively correlated with well-being